Uma mulher entre livros: Zila Mamede e o silencioso exercício de semear bibliotecas - Castro, Marize Lima de (2004)
Zila Mamede left a great contribution to education and culture in Rio Grande do Norte during the 60s, when she built the most important outdoor library from the state the Camara Cascudo s bibliography. It is this aspect of her work that this text tries to apprehend and narrate. Different approaches have brought Zila Mamede to academy, but her work as a librarian yet did not have had any study. Her pioneer work on organizing and preparing professionals to deal with these constructions full of books was waiting to be told. This work articulates itself with the political and cultural production of Natal during the 60, because it was essential to configurate the city at this time. It was also necessary to interview Zila Mamede s friends, relatives and the people who worked with her. This research also demanded a review of many memoirs by potiguares , and the examination of newspapers and magazines to enlighten the period